MARKETING PENDIDIKAN ISLAM DALAM KONTEKS INDUSTRIALISASI - Syafrawi, Syafrawi (Universitas Islam Madura, 2017)
The determination of an industrial location is determined by three factors, namely; first, the cost of transport. Second, labor, and third, deglomeration. Variations of the motive, having the same estuary is the achievement of a profitable business destination for the producers. A more comprehensive understanding, that the selection of industrial sites is determined by several factors, among others: first, endowment factors or known as natural resources and energy contained on the surface of the earth and contained therein. Second, the human resource factor. This factor becomes an option for producers by measuring the level of availability of large manpower and skill levels. Third, the capital factor, both physical and non-physical. Fourth, market and price factors. Fifth, agglomeration factor. This factor indicates the situation of centralizing economic activities in certain locations, particularly the center of agglomeration placed at one of the points with the lowest transportation costs. Sixth, the factor of government policy. The choice of location because of this factor became an alternative for producers to maintain and develop their industry although initially it was not profitable, but because of the motive of existence and protection of its industry, the economic consideration was temporarily suspended.